How Does Kyai Leadership Navigate the Digital Era in Shaping Religious Culture? - Mahmudah, Siti; Aminah, Siti; Azahra, Naila; Rosyadhi , Rozi Irfan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the implementation of kyai leadership management in shaping religious culture in the digital era, focusing on the Darussalam Islamic Boarding School, Tosaren Village, Kediri City. The qualitative approach is descriptive, with data collection techniques through observation, in-depth interviews, and documentation studies. The study results show that Kyai applies a combination of authoritative, charismatic, and democratic leadership styles in carrying out spiritual, organizational, and educational leadership functions. An authoritative, charismatic, and democratic leadership style in carrying out the functions of a spiritual, organizational, and educational leader. An authoritative leadership style will improve the discipline and attitude of the students in their daily lives. With a charismatic leadership style, a kyai can set a good example, be wise, inspire followers, and convey a meaningful message in the wider environment. With a democratic leadership style, kyai can think openly, keep up with the times, and involve related parties to collaborate and communicate to create a learning atmosphere in Islamic boarding schools. In addition, the importance of the kyai leadership style is open and adaptive, and they will be able to face challenges in the digital era. From this research, a kyai can adjust his leadership style to the development of technology and existing challenges to improve the quality of Islamic education and pesantren management and form the character of religious students.